Nucleosynthesis by accelerated particles in a bipolar Supernova explosion - Vernardos, G.; Goriely, S.; Lalazissis, G. (HNPS Advances in Nuclear Physics, 2020)
The most spectacular final phase of an evolved star, is the supernova explosion. It has been suggested by observations that such an event might not be spherically symmetric. This asphericity could be explained by the formation of jets of accel- erated particles by the explosion, which could interact with the stellar matter and give rise to a possible nucleosynthesis. Such a nucleosynthesis is studied. The fi- nal abundance pattern is shown to depend on the values of the model parameters adopted, especially the energy spectrum of the accelerated particles.